Molecular data from up to 130‐year‐old herbarium specimens do not support the presence of cherry powdery mildew in Australia. (1st December 2020) - Smith, Reannon L.; May, Tom W.; Kaur, Jatinder; Sawbridge, Tim; Mann, Ross; Edwards, Jacky
Abstract: A strain of Podosphaera clandestina has been highlighted as a priority pest threat to the Australian cherry industry. Australia currently has no records of powdery mildew on cherry ( Prunus avium ). P. clandestina is reported to cause disease on a range of Rosaceae genera including Crataegus and Prunus ; in Australia, P . clandestina has only been recorded on Crataegus . A recent species revision identified Podosphaera cerasi on P. avium as a separate species from P . clandestina . Therefore, a revision of which powdery mildew species is present in Australia on Crataegus is required to inform Australian plant biosecurity. Reference collection specimens from the Victorian Plant Pathology Herbarium (VPRI) recorded as Podosphaera spp. collected between 1889 to 2008 on cherry and three other host plant genera from Australia and overseas were sampled for DNA extraction and next‐generation sequencing (NGS). Sequence data from preserved specimens were successfully mapped to internal transcribed spacer (ITS) sequences of P . clandestina in the strict sense, P . cerasi, and P odosphaera prunicola, and chloroplast matK sequences were used to identify plant hosts. Australian specimens on Crataegus hosts were P . clandestina in the strict sense and specimens on Prunus from the USA were identified as P. cerasi and P . prunicola . The outcome of this study confirmed the powdery mildew on Australian Crataegus specimens to be P . clandestina and none of the cherry powdery mildews ( P odosphaera pruni ‐ avium, P. cerasi, or P . prunicola ) are present on Australian specimens in the VPRI collection, which suggests they are not present in Australia. Abstract : A molecular revision of Australian herbarium specimens confirmed Podosphaera clandestina in the strict sense on Crataegus and cherry‐infecting powdery mildews were absent from Australian specimens.